Pola Konsumsi Informasi Dan Pengenalan Berita Hoax Di Kalangan Generasi Usia Lanjut: Studi Kasus Pada Penggunaan Aplikasi Whatsapp - Septiana Devi Permatasari; S. Rouli Manalu (Interaksi Online, 2021)
Information consumption patterns are people's habits in receiving and using information that is seen based on the source of information used, the type of information received, the way they process information (asking, discussing, comparing information, or verifying through other sources of information or other media) and their responses when obtaining information (reading, muting, deleting or forwarding the message). The aim of the study is to describe the pattern of information consumption and recognising of hoax news in the elderly generation through the Whatsapp application that they use daily. The subjects of this research are informants who are 50 years old and over, and actively use Whatsapp as a medium for exchanging information. The result of the study show that Whatsapp is used by the older generation to fulfill their information needs. The informant said that messages obtained through Whatsapp were always up to date. Most of the informants have made Whatsapp the main medium to meet their information needs. The topic of health is the main topic that is most in demand by the elderly generation. The reason is because the topic is in accordance with what they need and is useful for their health. The next topics that interest them are religion and culinary. While other topics are entertainment, politics, and information related to job vacancies. When receiving information, the informant feels happy and will share it with his family or friends who are members of the same group. Informants feel that the information they share will be useful to others. The ability to recognize hoaxes from each informant is different, but the majority of informants are able to recognize the characteristics of the hoax news they receive. The length of use also affects their sensitivity to hoax news, the longer they have a Whatsapp account, the more they can identify hoax news or not. However, if they spread hoax information accidentally then they do not feel responsible for the message and leave it entirely to the reader.